At the first table : food and social identity in early modern Spain - Campbell, Jodi, 1968- (Lincoln : University of Nebraska Press, 2017)
"Research on European food culture has expanded substantially in recent years, telling us more about food preparation, ingredients, feasting and fasting rituals, and the social and cultural connotations of food. At the First Table demonstrates the ways in which early modern Spaniards used food as a mechanism for the performance of social identity. People perceived themselves and others as belonging to clearly defined categories of gender, status, age, occupation, and religion, and each of these categories carried certain assumptions about proper behavior and appropriate relationships with others. Food choices and dining customs were effective and visible ways of displaying these behaviors in the choreography of everyday life. In contexts from funerals to festivals to their treatment of the poor, Spaniards used food to display their wealth, social connections, religious affiliation, regional heritage, and membership in various groups and institutions and to reinforce perceptions of difference. Research on European food culture has been based largely on studies of England, France, and Italy, but more locally on Spain. Jodi Campbell combines these studies with original research in household accounts, university and monastic records, and municipal regulations to provide a broad overview of Spanish food customs and to demonstrate their connections to identity and social change in the sixteenth and seventeenth centuries"--
"At the First Table demonstrates the ways in which early modern Spaniards used food as a mechanism for the performance and maintenance of social identity"--
Machine generated contents note: 1. Basic Food Practices and Beliefs -- 2. Social Groups and Collective Identity -- 3. Status and Change -- 4. Vice and Virtue, Body and Soul.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
JSTOR
Keywords: Food habits -- Social aspects -- Spain -- History -- 16th century; Food habits -- Social aspects -- Spain -- History -- 17th century; Gastronomy -- Spain -- History -- 16th century; Gastronomy -- Spain -- History -- 17th century; Food -- Symbolic aspects -- Spain; Spain -- Social life and customs -- 16th century; Spain -- Social life and customs -- 17th century; Food habits - Social aspects; Cooking -- history; Habitudes alimentaires -- Aspect social -- Espagne -- Histoire -- 16e siècle.; Habitudes alimentaires -- Aspect social -- Espagne -- Histoire -- 17e siècle.; Gastronomie -- Espagne -- Histoire -- 16e siècle.; Gastronomie -- Espagne -- Histoire -- 17e siècle.; Aliments -- Aspect symbolique -- Espagne; Espagne -- Mœurs et coutumes -- 16e siècle.; Espagne -- Mœurs et coutumes -- 17e siècle.; HISTORY -- Europe -- Spain & Portugal; SOCIAL SCIENCE -- Sociology -- General; COOKING -- History; Food habits -- Social aspects; Food -- Symbolic aspects; Gastronomy; Manners and customs; Spain; 1500-1699; History